The Existence and Uniqueness of the Weak Solution for the Evolutionary Electrochemical Machining Problem (Journal of Partial Differential Equations, 2020)
A time dependent electrochemical machining problem, in which the cathode is fed towards the anode with a constant velocity, is studied. We prove the existence and uniqueness of the weak solution for the problem under the assumption that the cathode is C^{1+β} for some β ∈ (0,1).
Keywords: Evolutionary elliptic free boundary problem; electrochemical machining problem; existence and uniqueness